Comparative Study of Some Engineering Properties of Aluminium Roof Sheets Manufactured In Nigeria and China (International Journal of Engineering and Computer Science, 2015)
Man has utilized various natural resources through technological methods to create environmentally safe, effective roofing materials. The materials include straw, mud, wood, tile, metal, aluminium, etc. A good roofing material should adequately withstand the loads it is subjected to within its life span. This depends on the quality of the material such as tensile strength, density and material composition. Roof materials are often destroyed by wind and heavy rainfall in Nigeria. Nigeria imports most of her Aluminium roofing sheets from China. This research compares some Strength properties of aluminum roof sheets produced in Nigeria with that from China. Both samples were subjected to some laboratory tests. The mean specific gravity of the local and foreign roof sheets was found to be 2.64 and 2.61 respectively. The local sheet was found to be 14 per cent more elastic. The mean ultimate tensile strength for the local and foreign Aluminium Roof Sheets is 52 and 43 N/mm2 respectively. The average Young Modulus for the local and foreign materials is 190 and 225 N/mm2 respectively.